Implementation of Spinning Machine Technology for Purun Rope and Business Management Development for the "Nasti Purun" Weaving Group in Serdang Bedagai - Buchari; Hidayati, Juliza; Dilham, Ami (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Activities for the Purun Weaving Group aim to enhance the quality of products and marketing for the "Nasti Purun" Purun Weaving Group in the Cinta Air Village, Perbaungan District, Serdang Bedagai Regency, as well as support the government's enterprise development program. Several production technologies within the "Nasti Purun" Purun Weaving Group in Serdang Bedagai are currently conducted manually, particularly the process of making Purun rope bags. The spinning of Purun rope still involves the use of hands and feet, causing discomfort, fatigue, and even injury to the workers' hands and feet. The "Nasti Purun" Purun Weaving Group in Serdang Bedagai is in dire need of a Purun rope spinning machine. The specific objective of this activity is the acquisition of a Purun rope spinning machine and providing appropriate marketing methods along with basic accounting. The implementation method is carried out comprehensively, beginning with the application of Purun rope spinning technology and proper business management development, expanding the market area using online marketing (digital marketing) as an effort towards achieving one of the SDGs objectives, Decent Work and Economic Growth. This aims to enhance inclusive and sustainable economic growth, as well as decent work for all. These activities can have a positive impact not only on the target community but also on the university.